Evaluation of Spatio-Temporal Patterns of Predation Risk to Forest Grouse Nests in the Central European Mountain Regions - Cukor, Jan; Linda, Rostislav; Andersen, Oddgeir; Eriksen, Lasse Frost; Vacek, Zdeněk; Riegert, Jan; Šálek, Martin (Animals (Basel), 2021)
We evaluated the spatiotemporal patterns of predation risk on black grouse nests using artificial nests that were monitored by camera traps in mountain areas with a small extant (Ore Mts.) and already extinct (Jeseníky Mts.) black grouse population. The overall predation rate of artificial nests was 56% and we found significant differences in survival rate courses over time between both study areas (68% Ore Mts. vs. 41%, Jeseníky Mts.). Within the time required for successful egg incubation (25 days), nest survival probability was 0.32 in the Ore Mts. and 0.59 in Jeseníky Mts. The stone marten (Martes foina) was the primary nest predator in both study areas (39% in total), followed by common raven (Corvus corax, 25%) and red fox (Vulpes vulpes, 22%). The proportion of depredated nests did not differ between habitat types (i.e., open forest interior, clearing, forest edge), but we recorded the effect of interaction of study area and habitat. In Ore Mts., the main nest predator was common raven with seven records (37%). The Eurasian jay (Garrulus glandarius) was responsible for most predation attempts in Jeseníky Mts. (five records, i.e., 83%), while in the Ore Mts., most predation attempts were done by red fox (six records, i.e., 38%).